Application of Artificial Intelligence for livestock disease prediction - Suresh, K. P.; Dhemadri, Dhemadri; Kurli, Rashmi; Dheeraj, R.; Roy, Parimal (Indian Farming, 2019)
Diseases have emerged as a major constraint to the sustainable growth of the national economy. Several diseases have reduced the productivity of the livestock and have slowed the growth of the sector. Many diseases are linked to environmental deterioration and stress associated with farm intensification. According to the epidemiological triad, for a disease to occur it is the environment which helps the pathogen/vector to move towards the susceptible host. Thus based on the environmental parameters of the particular area early recognition of a serious or exotic animal disease can be done which is one of the most important factors influencing the chance of controlling the disease and reducing its economic and social impact on the whole country.